Ilex latifolia Thunb protects mice from HFD-induced body weight gain. Issue 1 (December 2017) - Wu, Hailan; Chen, Yue-Lei; Yu, Yueyuan; Zang, Jin; Wu, Yikuan; He, Zhao
Abstract Kuding tea is implicated in alleviating metabolic disorders in traditional Chinese medicine. However, the role ofIlex latifolia Thunb (kuding tea), one of the large leaf kuding tea species, in the prevention of the development of obesity remains to be determined. We show here that 7-week-old male mice treated with anIlex latifolia Thunb supplement for 14 weeks were resistant to HFD-induced body weight gain and hepatic steatosis, accompanied by improved insulin sensitivity.Ilex latifolia Thunb supplementation dramatically reduced the systemic and tissue inflammation levels of mice via reducing pro-inflammatory cytokine levels, increasing anti-inflammatory cytokine levels in the circulation and inhibiting p38 MAPK and p65 NF-κB signaling in adipose tissue. Together, these results indicate thatIlex latifolia Thunb protects mice from the development of obesity and is a potential compound pool for the development of novel anti-obesity drugs.